Validating The Questionnaire Measurement Scale of SME Owners' Perceptions and Intentions to Adopt QRIS - Azisma Nur Putri Ikwanto; Farida Indriani (LifeSciFi, 2023)
This study aims to assess the validity and reliability of a questionnaire designed to measure Micro, Small, and Medium Enterprises (MSME) owners' perceptions of Quick Response Code Indonesian Standard (QRIS) adoption, focusing on perceived usefulness, ease of use, digital literacy, and intention to adopt. The validity test was conducted using Pearson’s product-moment correlation, with results indicating that all items in the questionnaire are valid when the Pearson correlation exceeds the r-table value of 0.2787. The reliability test was conducted using Cronbach's alpha, where all items showed values greater than the minimum threshold of 0.60, indicating that the questionnaire is reliable. The findings show that MSME owners perceive QRIS as beneficial for enhancing transaction efficiency, facilitating customer reach, and achieving business objectives. Additionally, MSME owners find QRIS easy to use, with straightforward processes and clear interactions. Digital literacy plays a crucial role, as MSME owners demonstrate a basic understanding of QRIS and its business benefits. The study also reveals that infrastructure support, training, and social trends influence MSME owners' intention to adopt QRIS. These results suggest that the questionnaire is a reliable tool for understanding MSME owners’ perceptions and adoption intentions toward QRIS in Indonesia.